Evaluation of retinal nerve fiber layer and macula thickness, colour vision and electroretinogram in patients with acne vulgaris treated with systemic isotretinoin - Wahab, Nurul Zulaikha (2021)
Introduction Isotretinoin (13-cis-retinoic acid) is a synthetic retinoid that is used specially for treating acne vulgaris that does not respond to other therapies. Isotretinoin is an extremely effective systemic medication for acne vulgaris which is widely used. However, isotretinoin is also known to have a broad side effect including ocular toxicity. Some studies have shown its effect on retinal nerve fiber layer (RNFL) and ganglion cell layer and visual functions. Objectives This study was performed to evaluate RNFL and macular thickness, colour vision and electroretinogram (ERG) on systemic isotretinoin treatment in acne vulgaris patients. Methods Prospective observational cohort study involving patients with moderate to severe acne vulgaris on systemic isotretinoin was conducted at Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II from June 2018 till May 2021. All patients had to undergo a complete ophthalmologic examination. RNFL and macula thickness analysis using optical coherence topography (OCT), colour vision analysis using Farnsworth-Munsell 100 Hue test and ERG were performed before the start of treatment and at three months of treatment. Statistical analysis was done using SPSS Inc Version 26. Results Forty patients who were treated with 20 mg daily oral isotretinoin were enrolled in this study. The mean age of the patients was 26.88 (7.16) years (which is between 17-43 years). Measurements of mean RNFL and macula thickness before starting isotretinoin treatment was 93.88 (11.08) μm and 300.94 (14.66) μm respectively, while the mean RNFL and macula thickness at 3 months of treatment was 94.35(10.11) μm and 301.42(15.65) μm respectively. Measurements showed no statistically significant change between two measurements (p>0.05). The colour vision score was 76.30 (32.27) before starting treatment and 74.15 (24.17) at 3 months of treatment. The amplitude of a wave and b wave in ERG before starting treatment was measured as 269.45(57.00) μV and 450.48(70.07) μV respectively. Whereas the amplitude of a wave and b wave at 3 months of treatment was measured as 268.68 (55.13 μV) and 448.40 (69.91) μV respectively. No statistically significant differences were observed in the colour vision score and ERG amplitude at three months of treatment (p>0.05). Conclusion There was no statistically significant difference in mean RNFL and macula thickness, colour vision and ERG of acne vulgaris patients before and at three months of systemic isotretinoin treatment.